Three-dimensional assessment of hallux valgus correction using the Lapicotton technique - Jasper, Ryan; Mallavarapu, Vineel; Stebral, Hannah; Jones, Matthew; VandeLune, Christian; Schmidt, Eli; Talaski, Grayson; Fayed, Aly; Alencar Mendes de Carvalho, Kepler; Chun Kim, Ki; Barbachan Mansur, Nacime Salomão; Dibbern, Kevin; et al. (Journal of the Foot & Ankle, 2022)
Objective: The objective of the study was to assess the efficacy of the LapiCotton procedure on patients with hallux valgus (HV) combined with medial longitudinal arch collapse. Methods: Preoperative and postoperative weight-bearing computed tomography (WBCT) scans were obtained from patients with HV submitted to the LapiCotton procedure. Semi-automatic measurements were applied to 22 WBCT images across 11 patients enrolled in the study using a software package (Bonelogic, Disior™, Helsinki, Finland). Significance level was set at 0.05. Results: The hallux valgus angle (HVA) was significantly larger (p=0.026) in the preoperative group (Mdn = 27.52) than in the postoperative group (Mdn = 20). In addition, the Meary sagittal measurement was found to be significantly increased (p=0.033) in the preoperative group (Mdn = -14.28) when compared to the postoperative group (Mdn = -11.15). It was also observed that the intermetatarsal angle was significantly larger (p=0.003) in the preoperative group (Mdn = 15.68) compared to the postoperative group (Mdn = 11.26). Conclusion: The LapiCotton procedure effectively corrected radiographic parameters in patients with HV combined with the medial longitudinal arch collapse. Level of Evidence III; Therapeutic Studies; Comparative Retrospective Study.